2015
DOI: 10.1080/01635581.2015.1055368
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Indications of Parenteral Nutrition in an Acute Palliative Care Unit

Abstract: The aim of this study was to estimate the use of parenteral nutrition (PN) in advanced cancer patients enrolled in an acute pain relief and palliative care unit of a comprehensive cancer center and the appropriateness of the criteria to select patients for PN. Fourteen out of 750 patients (1.8%) admitted to an acute palliative care unit were administered PN. Patients were referred from various settings. The mean age was 58 yr (range 37-79), and 9 were males. The mean hospital stay was 7.7 days (range 3-14), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Most reports describing PN use in this population involve single centers with a small cohort of patients. One study, conducted in an inpatient palliative care unit, revealed that 1.8% of patients received PN during their stay in the unit 29 . However, some data suggest that PN use in palliative care may be more common than previously thought, with some variation across counties 20 , 30 .…”
Section: Question 9: Is Pn Appropriate For Patients In Palliative Care?mentioning
confidence: 99%
See 1 more Smart Citation
“…Most reports describing PN use in this population involve single centers with a small cohort of patients. One study, conducted in an inpatient palliative care unit, revealed that 1.8% of patients received PN during their stay in the unit 29 . However, some data suggest that PN use in palliative care may be more common than previously thought, with some variation across counties 20 , 30 .…”
Section: Question 9: Is Pn Appropriate For Patients In Palliative Care?mentioning
confidence: 99%
“…From an ethical and legal standpoint, there is no differentiation between withholding and withdrawing therapy 1 . However, once started, PN may be difficult to stop, as withdrawing an element of care carries greater emotional weight than withholding therapy 1 , 29 . Sensitivity to the cultural values and religious beliefs of patients and families is crucial in this situation.…”
Section: Question 9: Is Pn Appropriate For Patients In Palliative Care?mentioning
confidence: 99%